Tendon mechanobiology: experimental models require mathematical underpinning. - Thompson, M (2013)
Mathematical and computational modeling is in demand to help address current challenges in mechanobiology of musculoskeletal tissues. In particular for tendon, the high clinical importance of the tissue, the huge mechanical demands placed on it and its ability to adapt to these demands, require coupled, multiscale models incorporating complex geometrical and microstructural information as well as time-based descriptions of cellular activity and response.This review introduces the information sources required to develop such multiscale models. It covers tissue structure and biomechanics, cell biomechanics, the current understanding of tendon's ability in health and disease to update its properties and structure and the few already existing multiscale mechanobiological models of the tissue. Finally, a sketch is provided of what such models could achieve ideally, pointing out where experimental data and knowledge are still missing.